Experimental Analysis of Green Concrete Incorporating Industrial and Agricultural Wastes (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing demand for sustainable construction materials has encouraged the use of industrial and agricultural wastes as partial replacements for conventional concrete constituents. This paper presents an experimental analysis of green concrete incorporating selected industrial and agricultural waste materials with the objective of enhancing strength performance while reducing environmental impact. Various concrete mixes were prepared by partially replacing cement and fine aggregates with waste-derived materials in different proportions. Standard experimental tests were conducted to evaluate the mechanical properties of the developed green concrete, including compressive strength, split tensile strength, and flexural strength at different curing ages. The experimental results indicate that the incorporation of waste materials can significantly improve or maintain the strength characteristics of concrete when used in optimal proportions. Furthermore, the study demonstrates the potential of waste-based green concrete as a viable and eco-friendly alternative for conventional concrete, contributing to sustainable construction practices and effective waste management.